Legal Protection of the Defendant’s Property as Evidence in the Trial Process of Corruption - Ibnu Kholik; Edi Warman; Dedi Harianto (UNIFIKASI : Jurnal Ilmu Hukum, 2022)
Success in eradicating corruption can not only be judged by simply bringing the perpetrators to justice. This success is deemed insufficient if the state losses due to corruption committed cannot be recovered, so that success is considered sufficient, it must be able to confiscate the assets of the accused perpetrators of corruption in the trial, which will later be used as payment of compensation for state losses charged to the Defendant. With the reason for the payment of compensation for state losses, the Defendant's property was then confiscated, both used and obtained from a criminal act of corruption, as well as on the Defendant's property which was obtained not from a criminal act of corruption and has nothing to do with a criminal act of corruption. Corruption crimes examined in this study include corruption cases in the field of natural resources, there are several court decisions in natural resource corruption regarding replacement money. The purpose of this study was to determine the position of the evidence in the trial process and how the legal protection of the defendant's property was used as evidence in the corruption case. This research is descriptive, normative juridical research type through legislation and conceptual approach, using secondary data obtained through literature study and document study, then analyzed qualitatively. The conclusion of this study are that the principle of presenting evidence in court is to support the evidence of the defendant's actions, not to be used as collateral for the execution of the sentence, so that the defendant's property that is not related and is not the result of a criminal act of corruption cannot be used as evidence in court process;